JUMLAH DAN DISTRIBUSI STOMATA PADA TANAMAN PENGHIJAUAN DI KOTA TERNATE - Nurmaya Papuangan; Nurhasanah .; Mudmainah Djurumudi (UNIVERSITAS KHAIRUN, 2014)
Plant can absorb pollutan. Part of plant which absorb the pollutan were leaf. Plant can use as pollotan indicator such plant which growth aside street.The purpose of this study were to determine the number and distribution of stomatal of plants which grouth aside street at Ternate City. This research was a descriptive study. The data were collecting by couting the number of stomatal and its distribution by using replica and whole mount method. Such plants were used in this study were Ficus benjamina L, Callophylum inophyllum L., Acacia crassicarpa, Samanea saman and Arecaceae. The result of this study showed a varies of stomatal number and its distribution within five species plants Stomatal number on A. crassicarpa categorited into uncoonting both of upper adaxial and lower abaxial, F. benjamina L. had stomatal number very high at abaxial side than adaxial side, C. inophyllum L. had stomatal number on adaxial side higher than adaxial side in S. Saman, its stomatal number on adaxial side categorized uncoonting whereas adaxial side were low. The stomata number of Arecaceae were categorized moderate on abaxial side where as adaxial side were low. Stomatal distribution on F. benjamina L., C. inophyllum L., A. crassicarpa, S. saman were random wereas Arecaceae were aline.